Scimago Institutions Rankings for the Assessment of National Education System and Particular University - V. M. Galynsky; A. V. Zhuk (Moscow Polytechnic University, 2021)
The article analyzes the results of the Scimago Institutions Rankings for the entire period of its existence and presents the detailed description of the rating methodology and necessary condition for the inclusion in the ranking list, i.e. the publication of more than 100 works by university stuff in the Scopus database. There has been an almost twofold increase in the number of universities in the ten-year ranking lists. The article illustrates the dynamics for a number of countries and analyzes the reasons for their shifts. The competition between China and the United States is demonstrated. It is noted how the adoption of political decisions, such as the "May decrees" in the Russian Federation or projects "211", "985" in China increase the number of universities in the country participating in the ratings. Such countries as Vietnam, Iran, Indonesia succeeded in multiplying their positions in the university rankings. The article estimates the rate of growth in the number of publications for university in order to maintain its position in the scientometric rankings. The research conducts the analysis of the time required by the ranking agencies to implement and reflect the changes initiated by state competitiveness improvement programs.